Copper‐Decorated Magnetite Polydopamine Composite (Fe3O4@PDA): An Effective and Durable Heterogeneous Catalyst for Pyranopyrazole Synthesis. Issue 48 (20th December 2022) - Badbedast, Mehran; Abdolmaleki, Amir; Khalili, Dariush
Abstract: Synthesis of pyranopyrazoles using heterogeneous catalysts is among the most executed synthetic approaches in organic chemistry and has attracted much attention because of the atom economy and environmentally benign issues. Magnetite dopamine‐supported copper nanoparticles were created using a simple co‐precipitation technique and characterized by Fourier‐transform infrared spectroscopy (FTIR), x‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), and vibrating sample magnetometry (VSM). The catalytic activity of the Fe3 O4 @PDA/CuCl2 system was probed in the synthesis of structurally diverse pyranopyrazoles. It′s worth mentioning that the catalyst could be used at low loadings to produce pyranopyrazoles with high to acceptable in the absence of an external reducing agent. Additionally, the produced heterogeneous catalyst can be reused (by extracting with an external magnet) in six subsequent cycles without suffering a significant loss in catalytic activity. The high efficiency of the derivatives from about 70 % to 98 %, as well as the fact that the TON)1000–2500( and TOF)1000–5000 h −1 ) have attained the optimal amount, indicate the catalyst's high efficiency. Abstract : Deposition of copper on Fe3 O4 @PDA nanocatalyst as a natural and non‐toxic catalyst with the ability to reuse 6 times, which is used in the synthesis of the useful and biological substance piranoprazole.